Normocalcaemic primary hyperparathyroidism: what is the role of parathyroid surgery? - Aojula, Nivaran (Ther Adv Endocrinol Metab, 2021)
Primary hyperparathyroidism (PHPT) is classically associated with both an elevated or ‘inappropriately normal’ parathyroid hormone (PTH) level and raised serum calcium. However, in clinical practice, increasing numbers of patients present with raised PTH but normal serum calcium, renal function and vitamin D; this is known as normocalcaemic PHPT (nPHPT). Studies investigating the clinical presentation of this condition have shown that patients may present with hypertension, nephrolithiasis, impaired glucose tolerance, osteoporosis and fragility fractures. The prevalence of such complications in nPHPT is similar to that in classical hypercalcaemic PHPT (hPHPT). Although the National Institute for Health and Care Excellence (NICE) have developed guidelines for the management of PHPT generally, a consensus is yet to be reached on the optimal management of nPHPT specifically. A review of the literature on parathyroidectomy in the treatment of nPHPT revealed that nPHPT patients were more likely to present with multi-glandular disease and significantly less nPHPT patients had an intra-operative PTH fall of >50% compared with those with hPHPT. These findings demonstrate that patients with nPHPT are more likely to receive bilateral neck explorations and require remedial surgery compared with hPHPT patients. Following surgery, improvements in bone mineral density (BMD) and renal stones are generally observed in those with nPHPT. Where surgery is not possible, medical management with alendronate has been shown to be effective in nPHPT patients. Given the higher incidence of multi-gland disease and greater possibility of remedial surgery in nPHPT, careful consideration of risks and benefits should be made on an individualised basis and surgery should be performed by surgeons experienced in four gland exploration.